(untitled) - Franklin, Peter (Cambridge, 1997)
As a leading European conductor and the composer of enormous and controversial symphonies, Gustav Mahler (1860-1911) inspired mythologizers in his own lifetime. Some of them were personal friends, concerned with countering biased criticism of him in which German-nationalist, hide-bound traditionalist or anti-Semitic elements were often mixed. In this new biography, Peter Franklin reconfronts the myth of Mahler-the-misunderstood-hero and attempts to find the person, or persons, behind the legends. His illuminating biography shows Mahler to be a profoundly sensitive thinker and composer, a dictatorial conductor and husband, an iconoclast and paradoxically, a traditionalist.
Keywords: Composers,Nhà soạn nhạc; Biography,Tiểu sử; Austria,Áo